Sauna-Induced Body Mass Loss in Young Sedentary Women and Men - Robert Podstawski; Tomasz Boraczyński; Michał Boraczyński; Dariusz Choszcz; Stefan Mańkowski; Piotr Markowski (The Scientific World Journal)
The aim of the study was to evaluate the relationship between body mass index (BMI) and body mass loss (BML) induced by thermal stress in a dry sauna. The study was conducted on a group of 674 sedentary students, 326 women and 348 men aged 19-20. The correlations between BMI scores and BML were determined. The subjects were placed in supine position in a dry sauna for two sessions of 10 minutes each with a 5-minute break. The influence of BMI on the amount of BML in the sauna was determined by nonlinear stepwise regression. The smallest BML was noted in underweight subjects; students with normal weight lost more weight, whereas the greatest BML was reported in overweight and obese subjects. Persons with a high BMI are at higher risk of dehydration, and they should pay particular attention to replenishing fluids during a visit to the sauna. The proposed equations for calculating BML based on a person's BMI can be useful in estimating the amount of fluids that should be replenished by both men and women during a visit to a dry sauna.